The Value of Customer Cocreated Knowledge during the Innovation Process - Mahr, Dominik; Lievens, Annouk; Blazevic, Vera (The Journal of product innovation management, 2014)
Customer cocreation during the innovation process has recently been suggested to be a major source for firms' competitive advantage. Hereby, customers actively engage in a firm's innovation process and take over innovation activities traditionally performed by a firm's employees. Despite its suggested importance, previous research has revealed contradictory findings regarding its impact, the nature of involved customers, and the channels of communication that enable cocreation. To provide a more fine‐grained picture, customer cocreated knowledge is first delineated into its key value dimensions of relevance, novelty, and costs, and then their impact on various innovation outcomes is investigated. Next, the study examines the antecedent role of customer determinants; that is, lead user characteristics and customer–firm closeness, on these knowledge value dimensions. Finally, we explore how these effects are moderated by the type of communication channel used. An empirical validation of the conceptual model is performed by means of survey data from 126 customer cocreation projects. The data analysis indicates that customer cocreation is most successful for the creation of highly relevant but moderately novel knowledge. Cocreation with customers who are closely related to the innovating firm results in more highly relevant knowledge at a low cost. Yet, cocreation with lead users produces novel and relevant knowledge. These effects are contingent on the richness and reach of the communication channels enabling cocreation. Overall, the findings shed light on opportunities and limitations of customer cocreation for innovation and reconcile determinants originating in relationship marketing and innovation management. At the same time, managers obtain recommendations for selecting customers and communication channels to enhance the success of their customer cocreation initiatives.